Polarization properties of light scattered by a metallic cylinder - López-Morales, G.; Saucedo-Orozco, I.; Espinosa-Luna, R.; Zhan, Q.; Villa-Villa, F. (Revista Mexicana de Física, 2017)
The experimental determination of the angularly resolved Mueller matrix associated to light scattered by a metallic cylinder is reported. The angle-dependent values of depolarization index and Gil-Bernabeu theorem confirm there are not depolarization effects. To our knowledge, this is the cheapest and easiest way to generate uniform linear horizontal and vertical polarizations scattered angularly. A possible application associated to the use of plastic optical fibers acting like a polarization de-multiplexer is briefly discussed.